Changing Role of the University Teachers: An Agenda for Transformative Education - Pasa, Rajan Binayek; Kharel, Suman (Tribhuvan University Journal, 2020)
This library based paper appraises importance of transformative education in Nepalese context. In doing so, educational outcomes have been theorized based on Vedic educational philosophy, power and pedagogy as well as fourth goal of sustainable development (quality education for all). This paper comes up with conclusion that transformative education has been becoming international agenda for sustainable development. Nepalese policy also has focused on developing and utilizing human capital potentials. However, modern education system has been re/producing passive teachers and students even in Universities. Teachers are failed to produce critical students having fullest sense of civic virtues and justice that are enviable for maintaining just society. Thus, better to apply intrinsic, extrinsic and functional power and linking teaching with personal and social development while transmitting of knowledge in the process of socializing students and others. Government mechanisms also need to create conducive environment for letting university teachers to participate during policy formulation and implementation processes. Finally, it is better to apply contextual model for transformative education by the University teachers highlighted in this paper.